2004
DOI: 10.1161/01.cir.0000142866.50300.eb
|View full text |Cite
|
Sign up to set email alerts
|

Statins Enhance Migratory Capacity by Upregulation of the Telomere Repeat-Binding Factor TRF2 in Endothelial Progenitor Cells

Abstract: Background-Cultivation of endothelial progenitor cells (EPCs) leads to premature replicative senescence, limiting ex vivo expansion for potential clinical cell therapy. Recent studies have linked senescence to the dysfunction of telomeres, the "ends" of chromosomes, via the so-called mitotic clock or culture-induced stress. The purpose of this study was to elucidate a possible role of telomere biology in the functional augmentation of EPCs by statins. Methods and Results-Human EPCs were isolated from periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(130 citation statements)
references
References 55 publications
7
118
0
5
Order By: Relevance
“…Moreover, most of our patients have been treated with medications like statins and ACE inhibitors/ARBs, all of which possess antiinflammatory and antioxidant properties (30 -34). To the best of our knowledge, no data exist to suggest an effect of ACE inhibitors/ARBs on TRF length, while clinical and experimental data suggest that treatment with statins may have a protective effect on TRF attrition in human progenitor endothelial cells (35).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, most of our patients have been treated with medications like statins and ACE inhibitors/ARBs, all of which possess antiinflammatory and antioxidant properties (30 -34). To the best of our knowledge, no data exist to suggest an effect of ACE inhibitors/ARBs on TRF length, while clinical and experimental data suggest that treatment with statins may have a protective effect on TRF attrition in human progenitor endothelial cells (35).…”
Section: Resultsmentioning
confidence: 99%
“…103 Interestingly, statins also reduce senescence and stimulate proliferation of PB-EPCs by regulating the activity of telomerase and cell cycle genes. 89,104 Thus the therapeutic potential of endothelial progenitor cells could potentially be enhanced by noninvasive pharmacological manipulation and used to accelerate re-endothelialization of injured vessels and inhibit neointimal hyperplasia after revascularization procedures.…”
Section: Endothelial Cell Therapy For Vascular Repair and Bioengineermentioning
confidence: 99%
“…Pretreatment of endothelial progenitor cells with statins, eNOSoverexpression of PPAR-gamma agonists before transfer increases their migratory, invasive, and neovascularization capacity -effects that are mediated by activation of endothelial nitric oxide synthase (Shao et al 2008;Spyridopoulos et al 2004). Similary, own results showed that prestimulation of endothelial progenitor cells from diabetic individuals with the peroxisome proliferator activated receptor -agonist rosiglitazone, enhances nitric oxide availability and the in vivo endothelial repair capacity of these cells (Sorrentino et al 2007).…”
Section: Future Directions Of Cell Based-therapy For Ischemic Heart Dmentioning
confidence: 91%